CONCURRENT TREATMENT OF CHILDREN’S EPILEPSY AND DEPRESSION - Aliyeva, S.E. (World of Medicine and Biology, 2024)
Epileptic children suffer from depression, and this condition is not well diagnosed and treated, and this results in poor health. The purpose of this work is to evaluate the rate of depression in children with epilepsy and develop an integrated treatment plan. 156 children (aged 12–17 years) with epilepsy were evaluated for depression using Hamilton depression rating scale and the ICD–10 criteria. The current study establishes a high level of depression in children with epilepsy; 68 % of participants fulfilled the criteria for different degrees of depression. Out of the 106 patients diagnosed with depression, 83 had mild depression, 21 moderate and 2 had severe depression. Wilcoxon test showed significant reduction in depression severity after combined anticonvulsant and antidepressant treatment (p=0.048). This is especially important in children as the prevalence of epilepsy and depression is high, and both conditions should be treated concurrently. Depression in children with epilepsy should be diagnosed and treated as soon as possible to enhance neurological and psychiatric prognosis.